2014
DOI: 10.1007/s40266-014-0228-7
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-Gamma Agonists for Alzheimer’s Disease and Amnestic Mild Cognitive Impairment: A Systematic Review and Meta-Analysis

Abstract: There is insufficient evidence to support the use of rosiglitazone in aMCI and AD patients in order to improve cognitive performance. Nonetheless, the efficacy of pioglitazone seems to be promising, particularly for patients with comorbid diabetes, however this needs to be further confirmed by well-designed trials with large sample sizes. PPAR-γ agonists such as rosiglitazone and pioglitazone are generally well-tolerated in AD and aMCI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…Two recent meta-analyses of primarily small trials reported that pioglitazone may be beneficial for patients with mild-to-moderate AD, particularly in patients with comorbid diabetes [82,83].…”
Section: Ppar Agonistsmentioning
confidence: 99%
“…Two recent meta-analyses of primarily small trials reported that pioglitazone may be beneficial for patients with mild-to-moderate AD, particularly in patients with comorbid diabetes [82,83].…”
Section: Ppar Agonistsmentioning
confidence: 99%
“…These observations logically led to the idea of repurposing T2D drugs in AD (Yarchoan and Arnold, 2014). Insulin, thiazolidinediones and glucagon-like peptide-1 (GLP-1) analog are still the subject of clinical trials in dementia, albeit with mitigated results (Craft et al, 2012;Gejl et al, 2016;J. Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1 Numerous studies have demonstrated shared pathophysiological mechanisms between AD and diabetes mellitus (DM) such as oxidative stress, mitochondrial dysfunction, inflammation, and insulin resistance. 1 Numerous studies have demonstrated shared pathophysiological mechanisms between AD and diabetes mellitus (DM) such as oxidative stress, mitochondrial dysfunction, inflammation, and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is characterized by progressive cognitive and functional impairments due to the accumulation of neurofibrillary tangles and plaques. 1 Numerous studies have demonstrated shared pathophysiological mechanisms between AD and diabetes mellitus (DM) such as oxidative stress, mitochondrial dysfunction, inflammation, and insulin resistance. 2 Mild cognitive impairment (MCI) is characterized by cognitive impairment in the absence of significant functional decline; it is often prodromal to the development of AD and other forms of dementia.…”
Section: Introductionmentioning
confidence: 99%